Modeling and Inference Based on the Semantics of Monitoring of Human Vital Signs - Bastos, Alexsandro Beserra; Sene Júnior, Iwens Gervásio; Bulcão-Neto, Renato de Freitas (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
This paper contributes with a knowledge representation model of the human vital sign monitoring activity based on Semantic Web specifications for ontologies and Horn-like rules. The proposed model is founded in interviews with intensive care units professionals, medical and nursing literature, and the reuse of existing ontologies. As a result, this work contributes with an ontology describing vital signs, actors and temporal information involved in monitoring, a set of requirements underlying to that model, and dozens of Horn-like rules describing alarms and the respective abnormal values for each vital sign.